2013
DOI: 10.1371/journal.pone.0065100
|View full text |Cite
|
Sign up to set email alerts
|

The EhCPADH112 Complex of Entamoeba histolytica Interacts with Tight Junction Proteins Occludin and Claudin-1 to Produce Epithelial Damage

Abstract: Entamoeba histolytica, the protozoan responsible for human amoebiasis, causes between 30,000 and 100,000 deaths per year worldwide. Amoebiasis is characterized by intestinal epithelial damage provoking severe diarrhea. However, the molecular mechanisms by which this protozoan causes epithelial damage are poorly understood. Here, we studied the initial molecular interactions between the E. histolytica EhCPADH112 virulence complex and epithelial MDCK and Caco-2 cells. By confocal microscopy, we discovered that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…Trophozoites adhere to the epithelium at the cell–cell contact (Li et al, ; Martinez‐Palomo et al, ), through molecules such as the EhCPADH complex (Arroyo & Orozco, ), the Gal‐Gal/NAc lectin (Leroy et al, ; Petri, Haque, & Mann, ), occludin‐like protein, and others (Goplen, Lejeune, Cornick, Moreau, & Chadee, ; Ravdin & Guerrant, ; Reed et al, ; Rosales‐Encina, Meza, Lopez‐De‐Leon, Talamas‐Rohana, & Rojkind, ). Furthermore, during epithelial penetration, other parasite mechanisms are involved, such as the insertion of amoebapores into the host cell membrane (Leippe, ), the dephosphorylation and degradation of host cell proteins (Betanzos et al, ; Leroy et al, ), the actin‐bundling protein villin proteolysis (Leroy et al, ), the activation of epithelial caspase 3‐like to induce host cell death (Huston, Houpt, Mann, Hahn, & Petri, ), the remodelling of the extracellular matrix with the cysteine proteinase A5 (CP‐A5) participation (Thibeaux et al, ), and the elaborated host inflammatory response (Begum, Quach, & Chadee, ). Of relevance is that during early contact with trophozoites, tight junctions (TJs) are disrupted and transepithelial electrical resistance (TEER) decreases (Betanzos et al, ; Lejeune, Moreau, & Chadee, ; Leroy et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trophozoites adhere to the epithelium at the cell–cell contact (Li et al, ; Martinez‐Palomo et al, ), through molecules such as the EhCPADH complex (Arroyo & Orozco, ), the Gal‐Gal/NAc lectin (Leroy et al, ; Petri, Haque, & Mann, ), occludin‐like protein, and others (Goplen, Lejeune, Cornick, Moreau, & Chadee, ; Ravdin & Guerrant, ; Reed et al, ; Rosales‐Encina, Meza, Lopez‐De‐Leon, Talamas‐Rohana, & Rojkind, ). Furthermore, during epithelial penetration, other parasite mechanisms are involved, such as the insertion of amoebapores into the host cell membrane (Leippe, ), the dephosphorylation and degradation of host cell proteins (Betanzos et al, ; Leroy et al, ), the actin‐bundling protein villin proteolysis (Leroy et al, ), the activation of epithelial caspase 3‐like to induce host cell death (Huston, Houpt, Mann, Hahn, & Petri, ), the remodelling of the extracellular matrix with the cysteine proteinase A5 (CP‐A5) participation (Thibeaux et al, ), and the elaborated host inflammatory response (Begum, Quach, & Chadee, ). Of relevance is that during early contact with trophozoites, tight junctions (TJs) are disrupted and transepithelial electrical resistance (TEER) decreases (Betanzos et al, ; Lejeune, Moreau, & Chadee, ; Leroy et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during epithelial penetration, other parasite mechanisms are involved, such as the insertion of amoebapores into the host cell membrane (Leippe, ), the dephosphorylation and degradation of host cell proteins (Betanzos et al, ; Leroy et al, ), the actin‐bundling protein villin proteolysis (Leroy et al, ), the activation of epithelial caspase 3‐like to induce host cell death (Huston, Houpt, Mann, Hahn, & Petri, ), the remodelling of the extracellular matrix with the cysteine proteinase A5 (CP‐A5) participation (Thibeaux et al, ), and the elaborated host inflammatory response (Begum, Quach, & Chadee, ). Of relevance is that during early contact with trophozoites, tight junctions (TJs) are disrupted and transepithelial electrical resistance (TEER) decreases (Betanzos et al, ; Lejeune, Moreau, & Chadee, ; Leroy et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the trophozoites and their CM produced a substantial cytopathic effect and an important decrease of TEER in the RBMEC culture. Previous reports showed that the cytopathic damage produced by A. castellanii, E. histolytica, Toxoplasma gondii, and Giardia duodenalis in HBMEC and MDCK cells, was the result of the action of their proteases (Betanzos et al 2013;Briceno et al 2016;Cuellar et al 2017;Halliez et al 2016;Khan and Siddiqui 2009;Shibayama et al 2013). To evaluate the damage produced by the amoebic proteases, we preincubated the trophozoites and their CM with E-64 or Aprotinin and observed that the cysteine proteases inhibitor but not the serine proteases exerted a protective effect on the endothelial monolayer.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports showed that the cytopathic damage produced by A. castellanii , E. histolytica, Toxoplasma gondii, and Giardia duodenalis in HBMEC and MDCK cells, was the result of the action of their proteases (Betanzos et al. ; Briceno et al. ; Cuellar et al.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the rapid loss of TER and increases paracellular permeability. 47 Additionally, Eh contains an occludin-like protein which possibly functions to displace the host TJ occludin resulting in a decrease in TER. 48 The expression of TJ proteins has been studied in the context of a mouse colonic loop model using control animals and also mice lacking a bonafide mucus layer.…”
Section: Tight Junction Permeability and Ion Secretionmentioning
confidence: 99%